One-step synthesis of MOF-derived Cu@N-doped carbon composites as counter electrode catalysts for quantum dot-sensitized solar cells. (1st June 2021) - Xie, Yiling; Xue, Weinan; Wang, Yuan; Zhu, Wei; Wang, Wei; Li, Yan
Highlights: Facile one-step pyrolysis techniques were used to prepare the nitrogen-doped carbon supported Cu nanoparticles composite materials (Cu@N-C). A serious of Cu@N-C composites with rich Cu nanoparticles and nitrogen-doped graphitic carbon were employed as counter electrode catalysts for QDSCs. The QDSCs based on Cu@N-C-900/FTO CEs achieved a highest PCE of 8.63%, which is slightly higher than that of Cu@C/FTO CEs (8.20%) and CuS@g-CNx CEs (8.37%), and significantly higher than that of N-C/FTO CEs (6.52%). Abstract: The nitrogen-doped carbon supported Cu nanoparticles composite materials (Cu@N-C) have been recognized as the excellent counter electrode catalysts for quantum dot-sensitized solar cells (QDSCs). Herein, the Cu@N-C composites were synthesized via facile one-step pyrolysis of nitrogen-containing Cu-MOFs precursor. By controlling the reaction temperature from 600 to 1000 °C, the Cu@N-C-x (x is the pyrolysis temperature) catalysts are obtained. An ordered nitrogen-doped graphitized carbon lattice around Cu nanoparticles of the Cu@N-C-x improves the conductivity of counter electrodes (CEs), and uniform doping of nitrogen in the carbon enhances the wettability of the carbon material. The Cu@N-C-900/FTO CEs prepared exhibit higher electrocatalytic activity than both pristine N-C/FTO and Cu@C/FTO CEs, which could be ascribed to the synergistic effect between abundant Cux S catalytic active sites and nitrogen-doped graphitic carbon. It is noted that the Cu@N-C-900/FTO CEs also show superior catalytic activity compared to CuS@g-CNx/FTO CEs due to the higher specific surface area and porosity of the carbon skeleton. As a result, the QDSCs based on Cu@N-C-900/FTO CEs achieved the highest PCE of 8.63%, which is slightly higher than that of Cu@C/FTO CEs (8.20%) and CuS@g-CNx CEs (8.37%), and significantly higher than that of N-C/FTO CEs (6.52%). Graphical abstract: In this work, nitrogen-doped carbon supported Cu nanoparticles composite materials (Cu@N-C) was synthesized via facile one-step pyrolysis of nitrogen-containing Cu-MOFs precursor. Combining the advantages of Cu nanoparticles with the excellent electrocatalytic ability and nitrogen-doped graphitized carbon with abundant dopant active sites, the QDSCs based Cu@N-C counter electrodes exhibit a surprising maximum PCE of 8.63% measured at 100 mW/cm 2 illumination (AM 1.5G), which is slightly higher than that of Cu@C/FTO CEs (8.20%) and CuS@g-CNx CEs (8.37%), and significantly higher than that of N-C/FTO CEs (6.52%). Image, graphical abstract